TGF-β1 Induces Immune Escape by Enhancing PD-1 and CTLA-4 Expression on T Lymphocytes in Hepatocellular Carcinoma - Bao, Shixiang; Jiang, Xiaopei; Jin, Shuai; Tu, Peipei; Lu, Jingtao (Frontiers in Oncology, 2021)
Primary liver cancer (PLC) is one of the most common types of cancer worldwide. Hepatocellular carcinoma (HCC) accounts for approximately 90% of PLC cases. The HCC microenvironment plays an important role in the occurrence and development of HCC. Immunotherapy for the HCC microenvironment has become an effective treatment strategy. T lymphocytes are an important part of the HCC microenvironment, and programmed cell death 1 (PD-1) and cytotoxic T lymphocyte-associated antigen 4 (CTLA-4) are the main immunosuppressive molecules of T lymphocytes. Transforming growth factor β1 (TGF-β1) can inhibit the immune function of T lymphocytes and promote the occurrence and development of tumors. However, few studies have explored whether TGF-β1 can upregulate the expression of PD-1 and CTLA-4 on T cells. In this study, we showed that TGF-β1 upregulated the expression of PD-1 and CTLA-4 on T lymphocytes and attenuated the cytotoxicity of T lymphocytes for HCC cells in vitro and in vivo. In addition, TGF-β1 increased the apoptosis of T lymphocytes induced by HCC cells. Finally, we found that the mechanism by which TGF-β1 upregulates the expression of PD-1 and CTLA-4 on T lymphocytes may be related to the calcineurin-nuclear factor of activated T cells 1 (CaN/NFATc1) pathway. This study will provide some experimental basis for liver cancer immunotherapy based on the tumor microenvironment.